Pericytes: jack-of-all-trades in cancer-related inflammation - Moro, Marianna; Balestrero, Federica Carolina; Grolla, Ambra A. (Frontiers in Pharmacology, 2024)
Pericytes, recognized as mural cells, have long been described as components involved in blood vessel formation, playing a mere supporting role for endothelial cells (ECs). Emerging evidence strongly suggests their multifaceted roles in tissues and organs. Indeed, pericytes exhibit a remarkable ability to anticipate endothelial cell behavior and adapt their functions based on the specific cells they interact with. Pericytes can be activated by pro-inflammatory stimuli and crosstalk with immune cells, actively participating in their transmigration into blood vessels. Moreover, they can influence the immune response, often sustaining an immunosuppressive phenotype in most of the cancer types studied. In this review, we concentrate on the intricate crosstalk between pericytes and immune cells in cancer, highlighting the primary evidence regarding pericyte involvement in primary tumor mass dynamics, their contributions to tumor reprogramming for invasion and migration of malignant cells, and their role in the formation of pre-metastatic niches. Finally, we explored recent and emerging pharmacological approaches aimed at vascular normalization, including novel strategies to enhance the efficacy of immunotherapy through combined use with anti-angiogenic drugs.